Streptococcus pneumoniae Infection in Patients with Asplenia: A Spanish Perspective over a 25-Year Period - Enrique Gea-Izquierdo; Gil Rodríguez-Caravaca; Ruth Gil-Prieto; Valentín Hernández-Barrera; Ángel Gil- (MDPI AG, 2024)
Anatomical or functional asplenia constitutes a risk factor for Streptococcus pneumoniae (SP) infection, being more frequent in children and the elderly and in people with multiple comorbidities. We aimed to describe the impact of invasive pneumococcal disease (IPD) on the clinical features and outcomes of patients hospitalized for asplenia in Spain. Discharge reports from the Spanish Minimum Basic Data Set were used to retrospectively analyze hospital discharge data with a diagnosis of asplenia from 1997 to 2021. A total of 132,257 patients with asplenia (splenectomized/non-splenectomized) were identified from the Spanish database. Among the cases, 177 (37.5%) patients with splenectomy and 295 (62.5%) patients without splenectomy developed IPD. The clinical presentations (non-infection vs. infection) did not significantly differ between the two reference groups, except for patients with COPD, rheumatoid disease, AIDS, other neurological disorders, metastatic cancer, and drug abuse. The risk factors for IPD were also more frequently reported in patients without splenectomy (p < 0.001) and with comorbidities (p = 0.005). The study of patients with asplenia provides relevant information about the state of SP infection. This epidemiological tracking can serve to better understand the comorbidities that affect them, the risk factors for the disease, the prediction of antibiotic use, and vaccination in public health, among other factors.